Effect of Intravenous Infusion of Lidocaine Compared with Ultrasound-Guided Transverse Abdominal Plane Block on the Quality of Postoperative Recovery in Patients Undergoing Laparoscopic Bariatric Surgery - Sun J; Wang S; Wang J; Gao X; Wang G (Drug Design, Development and Therapy, 2022)
Jing Sun,1,2 Shan Wang,1,2 Jun Wang,1,2 Xiuxiu Gao,1,2 Guanglei Wang1,2 1Jiangsu Province Key Laboratory of Anesthesiology, Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of China; 2Department of Anesthesiology, The Affiliated Hospital of Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of ChinaCorrespondence: Guanglei Wang, Department of Anesthesiology, The Affiliated Hospital of Xuzhou Medical University, No. 99 Huaihai West Road, Xuzhou, 221000, People’s Republic of China, Tel +8613852087156, Email 13852087156@163.comPurpose: To investigate the effect of intravenous infusion of lidocaine compared with ultrasound-guided transverse abdominal plane (TAP) block on the quality of postoperative recovery and analgesic effect in patients undergoing bariatric surgery.Patients and Methods: Ninety-nine ASA II–III patients scheduled for elective laparoscopic bariatric surgery were randomized into the lidocaine group (group L), transverse abdominal plane block group (group T), and control group (group C). Group L: a loading dose of 1.5 mg/kg lidocaine was given at induction, followed by 2 mg·kg− 1·h− 1 maintenance until the end of surgery. Group T: ultrasound-guided bilateral administration of 0.25% ropivacaine in the transverse abdominal plane was given after induction of general anesthesia. Group C: no additional treatment was performed. Quality of recovery-40 (QoR-40) was assessed at 24 h after surgery. Consumption of propofol and remifentanil, visual analog scale (VAS) pain scores at rest at 0, 6, 12, and 24 h postoperatively, time to return of intestinal function, use of remedial analgesics within 24 h after surgery, adverse reactions were recorded.Results: Compared with Group C, Group L and Group T had higher QoR-40 scores at 24 h postoperatively, and the difference was statistically significant (P=0.002 and P=0.003, respectively). However, there was no difference between Group L and Group T (P=0.128). In addition, compared with those of Group T and Group C, VAS scores at 12 h and 24 h postoperatively were lower in Group L (P < 0.0166).Conclusion: Both intravenous infusion of lidocaine and ultrasound-guided TAP block provided good postoperative recovery and postoperative analgesia for patients with bariatric surgery, and intravenous infusion of lidocaine provided better analgesia at 12 h and 24 h postoperatively compared with TAP block.Keywords: lidocaine, TAP block, bariatric surgery, postoperative recovery, postoperative pain